Inventory of the county archives of Washington.
Includes: No. 1. Adams. -No. 2. Asotin. -No. 3. Benton. -No. 4. Chelan. -No. 8. Cowlitz. -No. 12. Garfield. -No. 17. King. -No. 21. Lewis. -No. 22. Lincoln. -No. 26. Pend Oreille. -No. 29. Skagit. -No. 31. Snohomish. -32. Spokane. -No. 33. Stevens. -No. 39. Yakima